Mutagenic Effect of Crude Oil on Accessions of Glycine max L. (Merril) (Biological Sciences - PJSIR, 2007)
Stud y of th e effects of crude oil on four accessions of Glycine max showed that the rate of germ i n ation , root length development and rate of cell division of the accessions decreased wi th i ncrea si ng concentration of crud e oi l. However , the extent of effects on the accessions varied showi n g differences in the abi l i ties of t h e accessions to survi ve i n crude oi l pol l uted sites, th e tol erance bei ng i n the order ofTG X I O 1 9-1 E < TGX 1 805-31 F < TGX 1 440-1 E < TGX I 448-2E su ggest i n g TGX I O 1 9- 1 E to be  the best i ndicator  of and TGX I  448-2E to be  the  best tolerant  accession  to the crude oi l  pol l ution.